Changing 'multi-Problem Families' - Developing a Multi-Contextual Systemic Approach - Eia Asen (Social Work and Society)
Over the past 30 years the Marlborough Family Service in London has pioneered multi-family work with marginalized families presenting simultaneously with abuse and neglect, family violence, substance misuse, educational failure and mental illness. The approach is based on a systemic multi-contextual mode and this chapter describes the evolving work, including the establishment of the first permanent multiple family day setting, specifically designed for and solely dedicated to the work with seemingly "˜hopeless' families. The ingredients of "˜therapeutic assessments' of parents and families are outlined and the importance of initial network meetings with professionals and family members is emphasized